Effect of Varying Levels of Turmeric Rhizome Powder on Some Blood Parameters of Broiler Chickens Fed Corn-Soybean Meal Based Diets - Emadi, M.; Kermanshahi, H.; Maroufyan, E. (International Journal of Poultry Science, 2007)
An experiment was conducted to study the effect of Turmeric Rhizome Powder (TRP) on some blood parameters in broiler chickens. A corn-soybean meal based diet containing levels of TRP (0.00, 0.25, 0.50 and 0.75%) in a completely randomized design with 4 treatments and 5 replicates of 10 birds each were fed to 200 day-old Ross male broiler chickens from 0-49 days of age. For measuring blood parameters (albumin, total protein, total cholesterol, HDL and LDL-cholesterol and triglyceride) at 21, 35, and 42 and red blood cells, hemoglobin and hematocrit value at 21 and 42 days of age, serum blood samples from each replicate of treatments were collected. Inclusion of TRP into the diets significantly increased total cholesterol, HDL-cholesterol and haemoglobin and decreased LDL-cholesterol, VLDL-cholesterol and red blood cells at 42 days of age (p<0.05). TRP also significantly decreased blood albumin (p<0.05). Under the condition of this study, it was concluded that TRP might have some positive effects on health status of the broiler chickens.